Karyometry of nuclear phenotypes in Cutaneous Squamous Cell Cancer - Bartels, Peter H. (2012)
OBJECTIVES: The objective of this study is to establish the karyometric characteristics of the two main nuclear phenotypes in cSCC lesions. MATERIALS AND METHODS: The clinical materials comprised 75 cases of cSCC, 38 with aggressive lesions and 37 with non-aggressive lesions. High-resolution images of 100 nuclei/case were recorded. The data were partitioned into four subgroups covering the range of lesion progression. Four discriminant functions were derived to distinguish aggressive from non-aggressive lesions. The most typical nuclei from the phenotype predominant in aggressive lesions, and from the phenotype predominant in non-aggressive lesions were separated out by thresholding on the discriminant function score axes. For these homogeneous sets of nuclei the karyometric features were computed. RESULTS: The nuclear populations in cSCC lesions are a very heterogeneous set. There are two axes of dispersion, along the line of lesion progression and between aggressive and non-aggressive lesions. The analysis faces the difficulty that lesions from both diagnostic categories contain nuclei of the same two phenotypes with the difference between categories consisting only of differences in proportion of the two phenotypes. CONCLUSIONS: The nuclei of the aggressive phenotype I and non-aggressive phenotype II have substantially different chromatin patterns and can be distinguished with a better than 90 % correct recognition rate.